2011
DOI: 10.1152/jn.00721.2011
|View full text |Cite
|
Sign up to set email alerts
|

Generalized vs. stimulus-specific learned fear differentially modifies stimulus encoding in primary sensory cortex of awake rats

Abstract: Chen CF, Barnes DC, Wilson DA. Generalized vs. stimulus-specific learned fear differentially modifies stimulus encoding in primary sensory cortex of awake rats. J Neurophysiol 106: 3136 -3144, 2011. First published September 14, 2011 doi:10.1152/jn.00721.2011.-Experience shapes both central olfactory system function and odor perception. In piriform cortex, odor experience appears critical for synthetic processing of odor mixtures, which contributes to perceptual learning and perceptual acuity, as well as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
100
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 50 publications
5
100
0
Order By: Relevance
“…One potential issue with these results lies in the fact that higher doses of oxotremorine have been shown to have analgesic effects in mice (Wess et al 2003), making them less sensitive to the shock. However, this is likely not an issue here as our dose of oxotremorine was lower than the effective doses for inducing analgesia in the above study.While these results demonstrate that olfactory generalization can be modulated by mAChRs during olfactory aversive learning, generalization can also be affected by other factors such as CS intensity, US intensity, and training conditions (Baldi et al 2004;Cleland et al 2009;Chen et al 2011). While our paradigm serves as the starting point for investigations into cholinergic influence on olfactory generalization, future experiments manipulating these factors are needed to fully characterize generalization of olfactory fear learning.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…One potential issue with these results lies in the fact that higher doses of oxotremorine have been shown to have analgesic effects in mice (Wess et al 2003), making them less sensitive to the shock. However, this is likely not an issue here as our dose of oxotremorine was lower than the effective doses for inducing analgesia in the above study.While these results demonstrate that olfactory generalization can be modulated by mAChRs during olfactory aversive learning, generalization can also be affected by other factors such as CS intensity, US intensity, and training conditions (Baldi et al 2004;Cleland et al 2009;Chen et al 2011). While our paradigm serves as the starting point for investigations into cholinergic influence on olfactory generalization, future experiments manipulating these factors are needed to fully characterize generalization of olfactory fear learning.…”
mentioning
confidence: 88%
“…While these results demonstrate that olfactory generalization can be modulated by mAChRs during olfactory aversive learning, generalization can also be affected by other factors such as CS intensity, US intensity, and training conditions (Baldi et al 2004;Cleland et al 2009;Chen et al 2011). While our paradigm serves as the starting point for investigations into cholinergic influence on olfactory generalization, future experiments manipulating these factors are needed to fully characterize generalization of olfactory fear learning.…”
mentioning
confidence: 88%
“…Recently, Luna and Morozov (2012) reported that the pPC differentially responds to amygdaloid versus cortical inputs by utilizing distinct local microcircuits. The pPC is thus an ideal locus to combine the sensory characteristics of the stimulus with its affective learned value transmitted by the BLA to keep the trace of this emotional olfactory memory as suggested by previous studies (Sevelinges et al 2004(Sevelinges et al , 2008(Sevelinges et al , 2011Barnes et al 2011;Chen et al 2011).…”
mentioning
confidence: 98%
“…Recently, Luna and Morozov (2012) reported that the pPC differentially responds to amygdaloid versus cortical inputs by utilizing distinct local microcircuits. The pPC is thus an ideal locus to combine the sensory characteristics of the stimulus with its affective learned value transmitted by the BLA to keep the trace of this emotional olfactory memory as suggested by previous studies (Sevelinges et al 2004(Sevelinges et al , 2008(Sevelinges et al , 2011Barnes et al 2011;Chen et al 2011).Most studies questioning the role of sensory cortices in fear conditioning have used auditory stimuli. These studies revealed that the lesion of auditory sensory cortices do not prevent the acquisition of auditory fear conditioning, thus arguing against their involvement in the learning (Campeau and Davis 1995; Armony et al 1997).…”
mentioning
confidence: 99%
“…Recent studies have shown that olfactory fear conditioning leads to generalized fear of similar odors (Chen et al 2011;Pavesi et al 2012). Additionally, it has been shown that this generalization is related to impairments in olfactory cortical odor discrimination (Chen et al 2011). Animals submitted to our generalization paradigm received pairings of E5 odor and foot shock, and were then tested with the trained and similar odors randomly in the same session.…”
Section: Odor Discrimination and Olfactory Memory Generalizationmentioning
confidence: 99%